A retrospective study assessing the characteristics of COVID‐19 convalescent plasma donors and donations. Issue 3 (14th December 2020) - Del Fante, Claudia; Franchini, Massimo; Baldanti, Fausto; Percivalle, Elena; Glingani, Claudia; Marano, Giuseppe; Mengoli, Carlo; Mortellaro, Cristina; Viarengo, Gianluca; Perotti, Cesare; Liumbruno, Giancarlo Maria
Abstract: Background: Although many trials are currently investigating the safety and efficacy of convalescent plasma (CP) in critically ill COVID‐19 patients, there is a paucity of ongoing and published studies evaluating the CP donors' side. This retrospective study reports the first Italian experience on CP donors' selection and donations. Methods: Patients aged 18‐68 years who had recovered from COVID‐19 at least 2 weeks previously were recruited between March 18 and June 30, 2020 in a study protocol at the Italian hospitals of Pavia and Mantova. Results: During the study period, 494 of 512 donors recruited were judged eligible and underwent 504 plasmapheresis procedures. Eighty‐five percent (437/512) of the CP donors were males. The average time between symptom recovery and CP donation was 36.6 (±20.0) days. Four hundred and eighty‐eight plasmapheresis procedures (96.8%) were concluded and each unit was divided into two subunits (total 976) with an average volume of 316.2 (±22.7) mL. Ninety‐three percent (460/494) of CP donors at the time of plasma donation had a neutralizing IgG titer ≥1:80. Plasmapheresis‐related adverse reactions occurred in 2.6% (13/504) of cases; all the reactions were mild and none required therapeutic intervention. Donors' age and COVID‐19 severity were positively associated with greater antibody responses. Conclusion: This study demonstrates the feasibility and safety of a pilot CP program conducted in Italy. The identification of factors (ie, age and severity of COVID‐19) positively associated with higher neutralizing antibody titers at the time of donation may help to optimize the selection of CP donors.